Optimization of biomass and hydrogen production by Anabaena sp. (UTEX 1448) in nitrogen-deprived cultures. (April 2018) - Vargas, Sarah Regina; Santos, Paulo Vagner dos; Zaiat, Marcelo; Calijuri, Maria do Carmo
Abstract: Hydrogen is a non-polluting source of energy, which is renewable and very abundant in the universe. Microalgae and cyanobacteria produce hydrogen by breaking down water and organic compounds. The aim of this research was to develop hydrogen production using cyanobacterium Anabaena sp. by nitrogen deprivation in two experimental phases of cultivation, optimizing its biomass from physicochemical variables. The experiment was carried out with axenic culture, in BG-11 medium, in triplicate, in two steps and under continuous illumination: in the first step, cultures were maintained in an aerobic condition until the first half of growth phase under nitrogen limitation; in the second step, the biomass was transferred, by centrifugation and cell wash, to anaerobic photobioreactors under nitrogen deprivation and the atmosphere was changed by argon for hydrogen production. Hydrogen was detected by gas chromatography and the hydrogen production parameters were tested using the Gompertz model and the volume by the general ideal gas equation. The optimization of biomass in the first step of cultivation increased its yield by 18.3% and heterocysts formation was 3.4 times higher in nitrogen privation conditions. Therefore, hydrogen production by cell increased 55.2% and the productivity 57.6% when compared to the culture of Anabaena sp. in control condition. The method and the strain were effective for hydrogen production and the pH, temperature and light intensity affected the improvement of this production and increased the biomass yield. Graphical abstract: Hydrogen concentration by cell (pmol cell −1 ) produced by Anabaena sp. (UTEX 1448) control condition and after optimization of the first and second steps. Bars show standard deviations (n = 3). Highlights: The influence of pH, light intensity, and temperature to improve biomass yield and consequent hydrogen production was clear. The method of nitrogen limitation in the first step of cultivation enhanced the heterocysts formation 3.4 times, contributing to the hydrogen production via nitrogenase. The optimization of biomass in the first step of cultivation increased its yield by 18.3%. The hydrogen production by cell increased 55.2% and the productivity 57.6% with the optimization.